DESAIN APLIKASI PRESENSI ONLINE BERBASIS WEB PADA PT PASSWORD SOLUSI SISTEM - Leon Fernando Wijaya; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Attendance and overtime are two crucial aspects of human resource management. This study takes PT Password Solusi Sistem, an IT solutions provider and systems integrator, as a case study. Currently, the company uses an online attendance application from an external service provider, but it faces challenges such as inefficient overtime calculations and limited feature customization. This research aims to design a web-based online attendance application that includes additional features not available in the current system. The development follows the Scrum methodology, beginning with user requirements gathered through interviews and progressing through the implementation of each application module. The resulting system design includes three user roles: Infrastructure Staff, Infrastructure Manager, and Human Resources Manager. Infrastructure Staff handle check-in and check-out attendance as well as manual overtime submissions, while the Infrastructure and Human Resources Managers have authority over user management, export of attendance and overtime data, shifts, and company holidays. Additionally, this study produces an interactive and user-friendly interface design.